Impact Of Covid-19 on Budget Preparation and Implementation In Nigeria, Private Universities: Evidence from Al-hikmah University - Suleiman , Yusuf; Ishola, Mustapha Adam; Tiamiyu , aji Solademi; Olawepo , Bello Zulaykha (International Journal of Educational Management, 2025)
The immediate consequences of the pandemic might be dire, but this crisis offers unique turning point; opportunities to learn, reshape, and build resilience into the educational system in Nigerian universities. Literature shows that the use c qualitative approach to investigate impact of COVID-19 on budget preparation i yet to be explored. In view of the foregoing, this study examined COVID pandemic and its impact on budget preparation and implementation in private universities in Nigeria with particular reference from Al-Hikmah University. Fo research questions were raised to guide the study. The population of consists of tie entire staff of the bursary department in Al-Hikmah University. Two non-probabili sampling techniques were used to select participants. Specifically, purposive arr convenience techniques were employed to select two principal accountants from the budget unit of the bursary department. An interview protocol tagged "Intervieu Protocol on Covid-19 and Budget Preparation (IPCBP) " was used to elicit relean. information for the study. The protocol was validated by experts with a view t ensuring the credibility of the items contained in the protocol while pilot sty we ascertained to ensure its trustworthiness. Data collected were analyzed usir; thematic method. Findings of the study revealed that the pandemic had impact c Al-Hikah University in many ways. They include decrease in recurrent and capita expenditure, retrenchment of both academic and non-academic staff, decrease i school fees payment, and low students’ enrolment among others. The study recommends that management of Al-Hiknah University should come up with another source of income to increase revenue drive. Also, all leakages in buudg